Compositional Changes Among Triglycerides and Phospholipids During FATP4 Sensitization with Palmitate Lead to ER Stress in Cultured Cells. Issue 5 (5th April 2019) - Seessle, Jessica; Liebisch, Gerhard; Schmitz, Gerd; Stremmel, Wolfgang; Chamulitrat, Walee
Abstract : FATP4 expression is upregulated in acquired obesity and polymorphisms in the FATP4 gene are associated with increased blood triglycerides (TG). Since non‐alcoholic fatty liver disease (NAFLD) is a manifestation of obesity, it is of interest to understand how FATP4 upon fat overload mediates alterations of lipids that lead to pathogenesis of fatty liver. A model system with FATP4‐overexpressed (FATP4) and control Huh‐7 cell lines is used to determine FATP4 response to palmitate (Pal). By lipidomics methods, cellular phospholipids (PL), neutral lipids TG, free cholesterol (FC), and cholesterol esters (CE) as well as lipoprotein secretion are determined. Without Pal, FATP4 cells show a significant increase of TG, phosphatidylcholine (PC), and the release of TG‐rich and cholesterol‐rich low density lipoproteins. Pal‐treated FATP4 cells show an increase of all PL subclasses except for phosphatidylserine (PS), TG, FC, and CE. By analyses of ratios among PL subclasses and between PL and neutral lipids, it is determined that FATP4 in response to Pal causes sequentially fatty‐acid channeling with a shift from PC and phosphatidylinositol (PI) to neutral lipids and from neutral lipids to PS and phosphatidylethanolamine (PE). This response is concomitant with an activation of CAAT/enhancer binding homologous protein and MAP Kinase JNK. Thus, FATP4 overexpression in response to Pal leads to enhancement of neutral lipids which play a central role in fatty‐acid distribution from PC and PI to PE and PS that led to an alteration of ER and mitochondrial membranes and subsequent stress signalling. Practical Applications : Activation of fatty acids by fatty acid transport proteins (FATP) plays an important role in development of obesity and NAFLD. This work highlights functional role of FATP4 on fatty‐acid distribution among neutral lipids and phospholipids upon fat overload. These changes may contribute to stress signalling in the pathogenesis of NAFLD. Compositional shift among total PL subclasses and neutral lipids. Abstract : Compositional shift among total PL subclasses and neutral lipids.